Analisis Kecukupan Beras di Kabupaten Asahan - abdur rasyid; Zulkarnain Lubis; Ahmad Rafiki (JURNAL AGRICA, 2023)
The standard area of paddy fields in Asahan Regency experiences degradation almost every year. Asahan District Government has made efforts to prevent the continuation of this problem. The aim of this study is to analyze the condition of rice sufficiency and the projection of rice sufficiency in Asahan District. This research is descriptive  used time series data for  years 2012-2021. The analytical method used is the calculation of rice availability based on the regulations of the minister of agriculture and projection analysis using Brown's Double Exponential Smoothing. The results showed that the availability of rice  tends to decrease throughout 2012-2021 and the need for rice  tends to increasing causes a deficit of sufficient rice every year in Asahan Regency. The projection of rice sufficiency in Asahan Regency until December 2024 show a deficit value meanwhile averages rice deficit every month reaches 3,129.27 tons/month.